(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Posthumanism is an opposite philosophical conception to humanism. It is an umbrella term that covers different philosophies like Antihumanism, Cultural Posthumanism, New materialism, Transhumanism and Artificial Intelligence (AI) Takeover.